Investigation of Copy Number Variations (CNVs) in South-East Asia (SEA) Plasmodium falciparum isolates and association with artemisinin resistance. - Guo, Weiliang. (2012)
Malaria is a global infectious disease cause by a parasite of the Plasmodium genus. Anti-malarial drug resistance has been rising and there is an urgent need to understand the mechanisms behind drug resistance. Copy Number Variations (CNVs) have been shown to contribute to genetic variations and associated to resistance in various anti-malaria drugs. Hence, we aim to study the CNVs of the deadliest strain of malaria parasite, Plasmodium falciparum, in South East Asia (Thailand, Cambodia and Laos) and to identify if there is any association between CNVs and artemisinin resistance. CNVs were shown to be enriched in sub-telomeric regions of P.falciparum and can arise when the parasites are subjected to selection pressure. A number of CNV genes were also identified to be associating to artemisinin resistance. Some of these may have involvement in various artemisinin resistance mechanisms previously reported. These suggested that artemisinin resistance phenotype in P.falciparum may be a multifactorial trait which involves multiple pathways. Furthermore, CNV profile showing several populations of the parasite with different sensitivity to artemisinin may allow the development of tools for estimation of artemisinin sensitivity of the parasite. This can greatly improve clinical diagnostic of malaria.